2023
DOI: 10.3390/polym15061517
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamaldehyde-Contained Polymers and Their Biomedical Applications

Abstract: Cinnamaldehyde, a natural product that can be extracted from a variety of plants of the genus Cinnamomum, exhibits excellent biological activities including antibacterial, antifungal, anti-inflammatory, and anticancer properties. To overcome the disadvantages (e.g., poor water solubility and sensitivity to light) or enhance the advantages (e.g., high reactivity and promoting cellular reactive oxygen species production) of cinnamaldehyde, cinnamaldehyde can be loaded into or conjugated with polymers for sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…Apart from its culinary applications, cinnamaldehyde has gained attention for its potential health benefits. Studies have suggested that it may have antioxidant, anti-inflammatory, and anticancer properties [393][394][395].…”
Section: Other Phenolic Compoundsmentioning
confidence: 99%
“…Apart from its culinary applications, cinnamaldehyde has gained attention for its potential health benefits. Studies have suggested that it may have antioxidant, anti-inflammatory, and anticancer properties [393][394][395].…”
Section: Other Phenolic Compoundsmentioning
confidence: 99%
“…To further augment the therapeutic potential of the hydrogel, the formulation incorporates cinnamaldehyde, a compound derived from cinnamon bark known for its antimicrobial and anti-inflammatory properties. Cinnamaldehyde has shown promise in preventing infection and reducing inflammation, critical factors that can impede the natural course of wound healing. , The inclusion of this natural compound aims to create a hostile environment for pathogens while simultaneously promoting an anti-inflammatory response, fostering an ideal milieu for tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamaldehyde has shown promise in preventing infection and reducing inflammation, critical factors that can impede the natural course of wound healing. 15,16 The inclusion of this natural compound aims to create a hostile environment for pathogens while simultaneously promoting an anti-inflammatory response, fostering an ideal milieu for tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Many naturally occurring drugs such as terpenoids, essential oils, and flavonoids have been shown to disrupt biofilm assembly and/or reduce EPS synthesis. Trans- cinnamaldehyde (CA), an α,β-unsaturated aromatic aldehyde, is the main component of cinnamon essential oil in China . It has been widely used in food, cosmetics, and other industries, and its anti-inflammatory, antioxidant, and antibacterial properties have been demonstrated. Previous studies have shown that CA has a wide antimicrobial spectrum, active against Salmonella typhimurium, Staphylococcus aureus (S. aureus), Escherichia coli (E.…”
Section: Introductionmentioning
confidence: 99%